Clima organizacional y su incidencia en la productividad del talento humano de la Escuela Técnica de Aviación Civil del Ecuador, año 2014 - Ruales Neira, Juan Carlos (2015)
This research was focused on the importance of owning Innovative model strategy that allows the correct development of the Workers of the Technical School of Civil Aviation of Quito in a suitable working environment on the basis of empowerment tool which is part to enhance the capabilities of and the results of teamwork, objectives itself to determine the impact of organizational climate in the performance of human talent in the School of Civil Aviation paragraph Improving productivity in the institution. Also measured the situation on real personal work climate and performance, just as diagnosis was made using the DAFO matrix of the institution to further develop Model Innovative Strategy To promote efficient growth of the organizational climate in the aforementioned institution. A methodology based on direct observation of the problem as well. The inductive-deductive method which served Moving from the expertise as surveys and interviews Knowledge of how the problem is generally used for the Conduct of Research. Base with the above deductions were prepared in the same manner the assumptions and Conclusions and Recommendations. Document Prepared work was structured in a manner that complies with the guidelines of this type of tool innovator which comprise the objects, features, phases, responsible and financing thereof, in order to provide goes the School of Civil Aviation appeal to help raise the productivity and keep the worker in a work environment according to your needs. Keywords: Organizational climate, productivity, human talent.